A Failure of Political Communication Not a Failure of Bureaucracy: The Danger of Presidential Misinformation During the COVID-19 Pandemic. Issue 6 (August 2020) - Hatcher, William
President Trump's communications during the novel coronavirus (COVID-19) pandemic violate principles of public health, such as practicing transparency and deferring to medical experts. Moreover, the president's communications are dangerous and misleading, and his lack of leadership during the crisis limits the nation's response to the problem, increases political polarization around public health issues of social distancing, and spreads incorrect information about health-related policies and medical procedures. To correct the dangerous path that the nation is on, the administration needs to adopt a more expert-centered approach to the crisis, and President Trump needs to practice compassion, empathy, and transparency in his communications.